Secularism, gender, and the state in the Middle East : the Egyptian women's movement - Al-Ali, Nadje Sadig (Cambridge Middle East studies ;, 2000)
A considerable literature has been devoted to the study of Islamic activism. By contrast, Nadje Al-Ali's book explores the anthropological and political significance of secular-oriented activism by focusing on the women's movement in Egypt. In so doing, it challenges stereotypical images of Arab women as passive victims and demonstrates how they fight for their rights and confront conservative forces. Al-Ali's book also takes issue with prevailing constructions of 'the West' and its perceived dichotomous relation to 'the East'. The argument is constructed around interviews which afford fascinating insights into the history of the women's movement in Egypt, notions about secularism and how Islamist constituencies have impacted on women's activism generally. The balance between the empirical and conceptual material is adeptly handled. The author frames her work in the context of current theoretical debates in Middle Eastern and post-colonial scholarship: while some of the ideas are complex, her lucid style means they are always comprehensible; the book will therefore appeal to students, as well as to scholars in the field.